A Political Companion to W. E. B. Du Bois - Bromell, Nicholas Knowles (Book collections on Project MUSE., 2018)
W.E.B. Du Bois was not a liberal, Marxist, radical, or republican-he was all of these and none. In 'A Political Companion to W.E.B. Du Bois', Nick Bromell assembles essays from both new and established scholars from a variety of disciplines to explore Du Bois's contributions to American political thought. The contributors establish a conceptual context within which to read the author, revealing how richly and variously he engaged with the aesthetic and theological modalities of political thinking and action. This volume further reveals how Du Bois's work challenges and revises contemporary political theory, providing commentary on the author's strengths and limitations as a theorist for the twenty-first century.